Criação de um painel de controle para prevenção da evasão escolar no Instituto Federal de Educação, Ciência e Tecnologia do Amazonas - Ferreira, Júlia Angélica de Oliveira Ataíde (2021)
The phenomenon of school dropout is a reality in Brazilian pedagogical spaces. This theme has been focused on in national studies with a view to identifying the main causes that lead students to discontinue their school life. This study aims to establish a conceptual definition regarding the issue of dropout, understand how dropout occurs at the Federal Institute of Education, Science and Technology of Amazonas (IFAM) and create a technological artifact that contributes to the management of teaching in the organization of pedagogical spaces for preventive action with this problem. The methodological procedure used was the ScientificTechnological Method (MC-T), developed by Nascimento-e-Silva (2012). The concepts concerning dropout were collected in databases and later organized in order to identify not only the content of the definitions but also their equivalence terms and attributes. Data collection was carried out by analyzing the minutes of class councils of the IFAM High School Technical Professional Education (EPTNM) courses, in the years 2018 and 2019, identifying the main causes of dropouts in that Institute. For empirical analysis, with the servers who work directly in education, an online questionnaire was self-administered, consisting of socio-institutional questions and related to possible causes of dropouts at the IFAM. The analysis of these responses occurred through the combination of the result (p-value) of 3 statistical tests, in order to identify the causes most strongly associated with school dropout at the IFAM. As a result, nine main causes of school dropout were obtained at the IFAM: social vulnerability, distance from home, pregnancy, class hours, lack of identity with the course, non-attendance, apathy, family problems and learning delay. After bibliographical, documental and field research analysis, a Control Panel was created as an educational product that will subsidize the work of professionals working in teaching management, to prevent school evasion within the IFAM. It is understood that this tool will be of great relevance not only for the Institute, but also for Professional and Technological Education (EPT) in Brazil, given the latent need for preventive strategies for the permanence and academic success of students, so desired by the network EPT.